Effects of Local Radiation Combined with Chemotherapy in the treatment of Patients with Extensive-stage Small Cell Lung Cancer - Di WU (Chinese Journal of Lung Cancer, 2015)
Background and objective Chemotherapy is a highly efficient primary treatment for extensive-stage small cell lung cancer (ES-SCLC). However, patients receiving such treatment are prone to develop drug resistance. Local treatment is palliative and thus can alleviate the local symptoms and improve quality of life, but limited evidence is available for prolonging survival. Hence, this study evaluated the role of local treatment in chemotherapy of patients with ES-SCLC. Methods A total of 302 ES-SCLC cases were enrolled in this retrospective study. Prognostic factors were analyzed by Kaplan-Meier and Cox multivariate proportional hazards model. Results Median progression-free survival (PFS) and median survival time (MST) of the patients were 4.4 and 10.4 months, respectively. 1-, 2-, and 3-year survival rates were 37.8%, 10.2% and 4.4%, correspondingly. The MST of the primary tumor radiotherapy plus chemotherapy group was 14.3 months, whereas that of the chemotherapy group was 8.2 months (P<0.01). The MSTs of multiple-site, single-site, and non-metastasis local treatments were 18.7, 12.3 and 8.9 months, respectively (P<0.01). The MSTs of initiative, passive, and non-metastasis local treatments were 16.0, 10.9 and 9.4 months, correspondingly (P<0.01). The MSTs of patients with prophylactic cranial irradiation (PCI) and those without PCI were 19.8 and 9.9 months, respectively (P<0.01). Primary tumor radiotherapy, metastasis local treatment, and PCI were independent prognostic factors for ES-SCLC. Conclusion Primary tumor radiotherapy, metastasis local treatment, and PCI can significantly improve survival in patients with ES-SCLC.